Kebijakan Pemerintah Dalam Program Daerah Peduli HAM di Provinsi Jambi - martin, joni; Mustofa, Muhammad; Ermasdon, Ermasdon; Arsyad, Arzi; Noviyanti, Noviyanti; Yuli Astuti, Diana; Siregar, Anhar; Arif fadly, Muhammad; Ridho Saputro, Muhammad; Saniati, Saniati; Kurniawan, Ade (Brida Provinsi Jambi, 2024)
Changes in the criteria for Human Rights Care based on Permenkumham number 22 of 2021 have caused many districts/cities to not get the status of Regency/City Caring for Human Rights, the number of regions that care about human rights decreased from 2020 and 2022. This evaluation aims to provide an overview of the implementation of Permenkum HAM Number 22 of 2021 in Jambi Province and what are the obstacles faced in its implementation as well as the relevance, sustainability and effectiveness of MMAF HAM programs/activities, in Jambi Province. Evaluation using an evaluative research approach using the Goal-freeevaluation model, descriptive analysis, evaluation carried out in Jambi Province with samples of Legal Bureaus and Legal Sections of Province/District/City Setda. From the results of the analysis, it is known that the process/mechanism for implementing the fulfillment of the Human Rights KKP Criteria in Jambi Province has run well, and is in accordance with the scheme that has been stipulated in the guidelines for the implementation of the Human Rights MMAF. However, there are several obstacles in its implementation such as a long and costly reporting mechanism; supporting data that is difficult to meet; the officer's lack of understanding of the form and supporting data; still not optimal socialization and technical guidance; and MMAF HAM activities have not become regional priority activities, which have an impact on budget availability in their implementation, from the results of the analysis also obtained several notes on the relevance, sustainability and effectiveness of MMAF HAM programs / activities in Jambi Province in the future, namely on the fulfillment of data supporting the right to legal aid and the right to diversity and pluralism these two aspects are partly difficult to fulfill in Jambi Province because they are hit by the availability of regulations. However, this does not significantly affect the sustainability and effectiveness of KKPHAM activity programs in Jambi province in the future. Keywords: Human Rights, Human Rights Care Criteria, Jambi